The Decade 1989-1998 in Spanish Psychology: An Analysis of the Development of Professional Psychology in Spain. - Santolaya Ochando, Francisco; Berdullas Temes, Manuel; Fernández Hermida, José Ramón (The Spanish Journal of Psychology, 2001)
Sin resumen